Assessing Attitudes, Knowledges and Practices Towards Food Poisoning Among Food Handlers and Students in Sarawak - Ling, Song Jing; Zamri, Hassan; Regina Garai, Abdullah (Secholian Publication, 2026)
Foodborne diseases are responsible for millions of deaths globally. Key factors contributing to these illnesses, as well as the high incidence of food poisoning among students, include improper methods of food preparation, unhealthy lifestyles, poor sanitation, and unsafe water resources. Moreover, the combination of food handlers mismanaging food and the students' and handlers' insufficient knowledge of food hygiene significantly exacerbates the food poisoning risk in school environments. The current study aims to assess the knowledge, attitudes, and behaviours regarding food hygiene among food handlers and students. The research method adopted in this study was the quantitative method to answer the research questions. This study utilised a non-probability sampling method, specifically quota sampling, after evaluating various sampling techniques. This study presented findings on the Knowledge, Attitudes, and Practices (KAPs) of both students and food handlers concerning hygiene awareness and safe food handling. The food handlers demonstrated poor personal hygiene practices, including improper handwashing technique and a lack of knowledge about the correct steps needed for effective handwashing. In addition, the food safety influenced by the canteen environment was statistically significant, whereas there was a difference in knowledge between male and female food handlers. Furthermore, the student’s knowledge was low regarding the towel used to wipe the hands could also be used to wipe the plate. The research might provide valuable insights and promote behavioural changes that could inform national health policy revisions, particularly in the area of food safety and regulations for preventing food poisoning.